Yield maximization through INM in sunflower (Helianthus annuus L.): Yield maximization through INM in sunflower (Helianthus annuus L.) - C RAVIKUMAR; M GANAPATHY (Journal of Oilseeds Research, 2020)
The experiment was conducted for two years in RBD with seven treatments of INM. The experiment was replicated four times. Sunflower was grown during summer after rice. Application of FYM @ 12.5 t/ha coupled with RDF increased the seed yield of sunflower.